ROLE OF JALUKAVACHARAN AND MAHAMANJISHTADI KWATH IN THE MANAGEMENT OF MUKHADUSHIKA W.S.R TO ACNE VULGARIS- A CASE STUDY - Jayant, Dhalpe Suchita; Chandurkar, Vivek S. (International Journal of Research -GRANTHAALAYAH, 2018)
Acne vulgaris is a disease of the pilosebaceous follicle characterized by noninflammatory (open and closed comedowns) and inflammatory lesions (papules, pustules, and nodules). There are four major factors involved in the disease production viz. increased sebum production, cornification of pilosebaceous ducts, microbial involvement and inflammation. This condition is found commonly in puberty. In Ayurveda, it is termed as Mukhadushika In Ayurveda Mukhadushika is described under the heading of Kshudrarogas. The Shalmali thorn like eruption on the face due to vitiation of Kapha, Vata and Rakta which are found on the face of adolescent are called as Mukhadushika or YuvanPidika. Although vata, kapha and rakta are mentioned as dosha-duṣya involved in the pathogenesis of the disease, pittaja symptoms are also found in the disease like daha and paka. Patient was suffering from Acne over face (Pidika), Burning sensation over face (Daha), Itching over face (Kandu), and Discolouration of skin (Vaivarnya) since 6 months. Patient was treated with jalukavacharan and mahamanjishtadi kwath.